Meninjau Ulang Teori Migrasi, di Mana Posisi Perempuan? Kritik, Tawaran, dan Implikasi - Khaerul Umam Noer (Antropologi Indonesia, 2010)
In its development, migration theories have been experienced flux and reflux–from economic point of view to individual as actor. Yet, development of migration theory disregards one important factor: women. This article has two objectives. Firstly, criticizing migration theory which neglects women, either as actor or subject who constructing migration theory. Secondly, offering feminist approach to migration theory and its implications. This article consists of three parts. Part one will explore classical migration theories which put emphasis on economy and contemporary migration theory which emphasizes migration actor. Part two is the critics of previous theories by showing women’s position in the migration theory. The last part discusses feminist approach and its implications on migration theory. Such critic is very important for migration theories exclude women voices and experiences.